2009
DOI: 10.1111/j.1442-9071.2009.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of ocular trauma in an urban south‐east Asian population: the Singapore Malay Eye Study

Abstract: One in 20 persons in this urban south-east Asian population had a history of ocular trauma. Younger persons, men and consumption of alcohol were risk factors for ocular trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 16 publications
3
37
0
1
Order By: Relevance
“…We have previously reported the prevalence and determinants of OT in Indian11 and Malay12 populations aged ≥40 years in Singapore. However, information is still lacking for the largest ethnic group, namely Chinese, who account for 74.1% of the population in Singapore 16.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the prevalence and determinants of OT in Indian11 and Malay12 populations aged ≥40 years in Singapore. However, information is still lacking for the largest ethnic group, namely Chinese, who account for 74.1% of the population in Singapore 16.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Singapore found that one in every 20 people had a history of eye trauma. Moreover, people’s occupation, gender, age, social economic status, alcohol consumption, smoking, and the type of housing were among the risk factors for eye trauma (5). …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] An eye injury that causes no light perception (NLP) typically carries an unfavorable prognosis, and NLP because of trauma is a common indication for enucleation. 11,12 Treatment of eyes with NLP after OGI continues to be a challenge for ophthalmologists throughout the world.…”
mentioning
confidence: 99%